2018
DOI: 10.1002/jia2.25120
|View full text |Cite
|
Sign up to set email alerts
|

Understanding reasons for discontinued antiretroviral treatment among clients in test and treat: a qualitative study in Swaziland

Abstract: IntroductionRetention on antiretroviral therapy (ART) is critical for the successful adoption of the test and treat policy by sub‐Saharan African countries, and for realizing the United Nations programme on HIV and AIDS target of 90‐90‐90. This qualitative study explores HIV positive clients’ reasons for discontinuing ART under the Max ART test and treat implementation study in Swaziland.MethodsClients identified as lost to follow‐up (LTFU) in the programme database, who had initiated ART under the interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 24 publications
3
37
0
Order By: Relevance
“…As in other studies, fear of disclosure of HIV status and the stigma associated with disclosure was an important barrier to accept this care closer to home. 32 This was not only found to be a barrier to get supply with ART, but also to discuss concerns and get information on the disease and treatment. 31 33 Contrary to a previous study, 34 patients valued the competence of HCPs highly.…”
Section: Discussionmentioning
confidence: 99%
“…As in other studies, fear of disclosure of HIV status and the stigma associated with disclosure was an important barrier to accept this care closer to home. 32 This was not only found to be a barrier to get supply with ART, but also to discuss concerns and get information on the disease and treatment. 31 33 Contrary to a previous study, 34 patients valued the competence of HCPs highly.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for this finding is that HIV-positive women who externally migrated away from the study area, mainly seeking economic and educational opportunities in larger cities, might have had difficulty accessing care in a new environment. A recent mixed-method study in Swaziland reported that PLWH who were lost to follow-up from HIV care described mobility as the first factor that affected their falling out of the care [38]. It is also possible that HIV-positive women might have self-selected into migration, as seen among HIV-positive individuals in Malawi [19].…”
Section: Discussionmentioning
confidence: 99%
“…We must consider time as well as space when conceptualizing and examining how migration might affect HIV prevention and care, including Universal Test and Treat (UTT) interventions. Forms of population mobility, especially in sub‐Saharan Africa, are complex and often characterized by multiple rounds of travel, seasonal migration or movement events in time . Circular migration, where migrants leave home to work (or for other reasons) but frequently return home before leaving again, is also common, especially in South Africa .…”
Section: Timementioning
confidence: 99%